Gatunek codzienności - Todorov, Tzvetan (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The present essay shows the new genres of the seventeenth century Dutch painting (portrait, landscape and genre painting), viewed as painting of everyday life, as an alternative proposition to the historical painting then dominant in the academic categorization. What used to be marginal, peripheral and of secondary importance became the main motif in the majority of Dutch painting. Minor genres came to prominence and acquired autonomous status. The interest in the elements of everyday life could be traced in European art earlier but it was the seventeenth century Dutch artists that ultimately led “low” and realistic subject themes to come into their own commercially and artistically. Occasionally, even religious themes were presented as genre scenes, thus introducing to the presented images an air of ambivalence. In the works of Dutch painters, the uniqueness of high subject themes was opposed by pictures of everyday life and the repetitiveness of everyday domestic activities, not shunning, however, the allegorical potential contained in some of the depictions.